A Shunt Active Power Filter for 12 Pulse Converter Using Source Current Detection Approach - Rajesh T; Nirmalkumar A (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
A shunt Active Power Filter (APF) with current detection at the source side is considered as a closed-loop system from the view of the whole power distribution system, which is expected with better harmonics filtering performance compared with conventional current detection methods such as load current detection and open loop control.  This paper introduces an efficient source current detection method (direct) control scheme to mitigate the grid current harmonics generated by the twelve pulse converter.  The proposed system uses Control Rectifier (12 –pulse converter) which efficiently regulates the DC voltage by varying the angle of each 6 pulse converter. Moreover, the proposed system uses three winding transformer which eliminates the harmonics during equal angles switching at each six pulse converter which in turn simplifies the operation of the SAPF. The proposed system is simulated in MATLAB SIMULINK to evaluate the performance of the proposed system.